2021
DOI: 10.1002/cam4.3803
|View full text |Cite
|
Sign up to set email alerts
|

Digital breast tomosynthesis compared to diagnostic mammographic projections (including magnification) among women recalled at screening mammography: a systematic review for the European Commission Initiative on Breast Cancer (ECIBC)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…Rigorous studies that enroll screening populations and report advanced cancer detection, morbidity, and mortality outcomes from multiple rounds of screening are needed to overcome persistent limitations in the evidence on breast cancer screening. Multiple screening rounds are essential to determine whether a screening modality or strategy reduces the risk of advanced cancer by detecting early cancers that would otherwise have progressed (stage shift), potentially reducing breast cancer morbidity and mortality …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigorous studies that enroll screening populations and report advanced cancer detection, morbidity, and mortality outcomes from multiple rounds of screening are needed to overcome persistent limitations in the evidence on breast cancer screening. Multiple screening rounds are essential to determine whether a screening modality or strategy reduces the risk of advanced cancer by detecting early cancers that would otherwise have progressed (stage shift), potentially reducing breast cancer morbidity and mortality …”
Section: Discussionmentioning
confidence: 99%
“…Study-defined advanced breast cancer outcomes were used when this outcome was not reported (eg, stage II or higher). Invasive breast cancer detection outcomes from multiple screening rounds can indicate whether a screening modality or strategy reduces the risk of advanced cancer by detecting early cancers that would otherwise have progressed (stage shift), thereby potentially reducing breast cancer morbidity and mortality …”
Section: Methodsmentioning
confidence: 99%
“…DBT represents a mammographic technique, involving mammograms from different angles to create computed tomosynthesis layered reconstructions of the breast 11 , 12 . Especially in the case of inhomogeneously dense breast parenchyma, DBT shows diagnostic advantages over conventional DM 8 , 13 17 . In detection of microcalcifications it shows similar results as DM 18 22 .…”
Section: Introductionmentioning
confidence: 99%